Criptografia: uma nova proposta de ensino de matemática no ciclo básico - Pereira, Nádia Marques Ikeda [UNESP] (2015)
The goal of this work, was highlight the cryptography as a way to improve the teaching of mathematics, important historical aspects showing were listed showing the cryptography evolution. The great importance of the cryptography's development in human history and the Mathematics required for this development. Showing also that the more mathematics is improve, the man has more way to encryption's development and then ensure the security of information. By the other hand, many mathematical concepts used in cryptography are part of the educational grade math. This way, mathematics concepts are associates with a applied form in cryptography now, makes the most significant learning experience for the student